Real Time Characterization of BA.2.86 and Its Variant (JN.1) in Senegal Using Midnight Protocol - Abdou Padane; Marilyne Aza-Gnandji; Seyni Ndiaye; Marièma Sarr; Cyrille Kouligueul Diedhiou; Astou Gueye; Yacine Amet Dia; Aminata Mboup; Abdoulaye Samba Diallo; Ousmane Diop; Ambroise Ahouidi; Papa Alassane Diaw; et al. (International Journal of Vaccines, 2024)
During the week ending August 13th, 2023, the most prevalent variant of interest (VOI), uploaded to GISAID, was the BA.2.86 variant. This SARS-CoV-2 Omicron lineage was described as the first phylogenetically distinct from the currently circulating SARS-CoV-2 Omicron XBB lineages, including EG.5.1 and HK.3. Compared to the XBB and BA.2 lineages, the BA.2.86 possesses more than 30 mutations in the Spike (S) protein, suggesting a significant potential for immune evasion. The BA.2.86 variant evolved and its descendant, JN.1 (BA.2.86.1.1) appeared in late 2023 and is currently classified as the new variant of interest by the WHO. Here, we carried out the characterization of the BA.2.86 SNPs (the JN.1 variant), which we most identified in Senegal from samples collected during December 2023 and January 2024. Nine of the sequences of these JN.1 variants that we identified have been published and are available on GISAID (EPI_ISL_18783717 to EPI_ISL_18783733). Despite the great immune invasion capacity of this BA.2.86 variant and its JN.1 descendants, it is important to note that Spike protein is also targeted by existing vaccines and current vaccines should act against these VOI.
Keywords: BA.2.86.1.1; JN.1; Lineages; Omicron variant; Sars-CoV-2